A 73‐year‐old man with loss of consciousness during treatment for miliary tuberculosis. Issue 6 (25th May 2022) - Ohgiya, Masahiro; Sasaki, Yuka; Yamane, Akira; Nakamura, Sumie; Matsui, Hirotoshi
Key message: Miliary tuberculosis is often associated with cerebral tuberculoma, which can manifest during treatment. We present images of a patient with cerebral tuberculoma detected due to emerging neurological symptoms during treatment of miliary tuberculosis. Abstract : We present images of a patient with cerebral tuberculoma detected due to emerging neurological symptoms during treatment of miliary tuberculosis.